Analysis of eye language in the biography and words of the Prophet (PBUH) - Ramazan Rezaei (Religion & Communication)
Analysis of eye language in the biography and words of the Prophet (PBUH)AbstractCommunication is the process of sending and receiving messages that are sometimes formed in the form of words and sometimes in a form other than words. The effect of non-verbal communication on the audience and the recipient is more than verbal communication. Nonverbal communication is the use of different parts of the body to receive and send messages. Among the types of non-verbal communication, in other words, the use of body language in the communication process, "look language" or eye communication has always been of paramount importance. It seems that the importance of this issue has been raised in religious texts and it has been used well to strengthen communication with the audience. Accordingly, in the present article, an attempt has been made to use the structure of eye contact or the language of gaze in the biography and words of the Prophet (PBUH), using the analytical-descriptive method, with the question of how the language of gaze is manifested in the biography and words of the Prophet. Found ?. The findings of this study indicate that whenever the eye and the gaze sit on the bed of "speech", it conveys the message wisely while also containing a symbolic and sign language.